The Miners of Petorca Against the Mayor José de Ahumada: Neighborhood and Political Culture of Groups in the Norte Chico (1725-1728) - Girón, Nicolás (Revista de Historia Social y de las Mentalidades, 2024)
The article analyzes the group political culture as interpretative key in microhistory approach of a judicial file in Petorca, of the first quarter of eighteenth century. Through the contextual study of social relations that are recognized in the case, the autor describes the importance that had social membership from a miners group in develop for their demand against a local judge. The conclusions suggest to recognize another way for historical study for institutions, the justice and authority’s role, and the value for everyday life to understand political phenomena in tardo-colonial Chile.